Upaya Mewujudkan Pendidikan Karakter Bangsa dalam Proses Kegiatan Belajar Mengajar di Sekolah Menengah Kejuruan Negeri 3 Karang Baru Aceh Tamiang - Roro Sri Hariyani (Universitas Negeri Medan, 2019)
The purpose of this study is to: Improve understanding, skills, implementation of the Karang Baru Vocational School Teacher 3 in the Teaching and Learning process, especially in the planting of national character values of the nation's character building values. Whereas the general objective of this school action research activity is to find out and to what extent the application of National Character Education in Teaching and Learning Activities (KBM) at Karang Baru 3 Vocational School in Aceh Tamiang Regency. The results of the analysis show that an increase in teacher understanding and skills regarding the application of national character education in teaching and learning has implications for increasing student participation or activity as well as the implementation of national character development values, such as hard work, cooperation, mutual respect, discipline, honesty, creativity , curiosity, love to read, care for the environment, the spirit of nationalism, love for the country, friendliness, love to read, social care, tolerance, religiousness, independence, and peace of mind. The conclusion obtained from the School Action Research (PTS) is that through the guidance activities of teaching and learning process of national character values, it has been well implemented and contributes to improving teacher understanding and skills regarding the application of national character education in teaching and learning activities.